2019
DOI: 10.1021/acs.jpcc.9b05030
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Mechanisms and Interfacial Behaviors of Sodium Silicate Glass in an Aqueous Environment from Reactive Force Field-Based Molecular Dynamics Simulations

Abstract: Corrosion of silicate glasses in aqueous environment is common and it impacts many physical and chemical properties of these materials that have wide ranges of industrial and technological applications. However, the corrosion mechanisms of silicate glasses remain relatively poorly understood due to complicated interfacial reactions and transport behaviors. Here, we have employed molecular dynamics simulations with the recently developed reactive force field to investigate the sodium silicate glass and water in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 29 publications
(47 reference statements)
5
34
0
Order By: Relevance
“…With higher concentration of Na 2 O, the silanol concentration has a lower peak at the surface with a deeper penetration inside the glass, which is consistent with the surface concentration of silanols seen in Figure A. The silanol profile usually follows the water profile in all the systems and can be attributed to water penetration resulting in silanol formation by protonation of an NBO, which is one of the mechanisms of silanol formation . However, in some of the glasses silanol formation was observed more than 3 Å beyond the depth of penetration of water.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…With higher concentration of Na 2 O, the silanol concentration has a lower peak at the surface with a deeper penetration inside the glass, which is consistent with the surface concentration of silanols seen in Figure A. The silanol profile usually follows the water profile in all the systems and can be attributed to water penetration resulting in silanol formation by protonation of an NBO, which is one of the mechanisms of silanol formation . However, in some of the glasses silanol formation was observed more than 3 Å beyond the depth of penetration of water.…”
Section: Resultssupporting
confidence: 78%
“…This demonstrates that silanol formation by mechanisms other than by dissociation of water molecule. We verified that the silanol formation in this particular case was by proton transfer between NBO's which is an experimentally established phenomenon . A qualitative snapshot of proton transport is shown in Figure B.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Thus, it can be concluded that the MD simulation results from the Teter potential would be inadequate to describe the structural features of glass that are relevant to the vibrational spectra. It is known that the partial charge pairwise Teter potential can generate reasonable short and medium range structures that are comparable to experimental data for sodium silicate glasses and, as a result, it has been widely used in the structural studies of silicate glasses . However, the fixed charge potential does not take into the ion polarization effect, which plays an important role in the vibrational spectra of the glass networks.…”
Section: Resultsmentioning
confidence: 97%
“…A more detailed atomic structural analysis on the ReaxFF modeling of sodium silicate glass can also be found in Ref. [28].…”
Section: Methodsmentioning
confidence: 99%